Impacts of real estate development on the greater Abidjan factory in Ivory coast - DEKI, Kouakou Tehua Pierre; Bénoît, DANVIDE T.; ZINSOU-KLASSOU, Kossiwa (Edelweiss Applied Science and Technology, 2025)
African cities are experiencing population growth. This growth generates housing problems that are somewhat resolved by real estate development. The city of Abidjan has benefited from a significant number of real estate developments that have contributed to its creation. The objective of this article is to highlight the contribution of real estate development to the creation of Greater Abidjan. Through a methodology combining qualitative and quantitative aspects, we have arrived at results indicating that real estate development has had a considerable social impact as well as spatial effects on the urbanization of Greater Abidjan.